Agriculture and Climate Change in Africa: Expert Meeting - #cop19 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Experts from five sub-regions of Africa (Northern, Western, Central, Eastern and Southern) discussed the current: a) State of African agriculture, b) Vulnerabilities, impact and adaptation strategies for a climate resilient agriculture c) Opportunities for adaptation co-benefits in agriculture d) Enabling framework to accelerate climate change adaptation and f) Agriculture issues under the UNFCCC process. Successful adaptation case studies for a climate resilient agriculture will also be highlighted. This was during a side meeting held during pre- #COP19. Photos: V. Atakos (CCAFS)